Gestión para la categorización de áreas protegidas privadas en la provincia de El Oro - Espinoza Murillo, Paola Lisseth (My University, 2021)
The province of El Oro has ecosystems that have physical, climatic, geomorphological and biological characteristics that make them areas of environmental value for the State, this case study is based on the management for the categorization of private protected areas in the province of El Oro where each of the essential instruments in the management of private protected areas APPRI in the province of El Oro will be analyzed in the declaration of subsystems of the National System of Protected Areas. This research aims to provide a practical and accessible guide on the requirements and steps to be followed by the National Environmental Authority for the categorization of protected areas. Due to the scarce information available to the national population interested in applying their territories as APPRI, a bibliographic research has been carried out based on scientific articles and data taken from the Directorate of Forests of the Ministry of Environment and Water, of this In this way, the methodology applied to the bibliographic approach research was born through an analysis and synthesis for which we obtained results through an organization chart that indicates each of the steps requested for the categorization of the APPRI subsystem.
La provincia de El Oro cuenta con ecosistemas que poseen características físicas, climáticas, geomorfológicas y biológicas que los convierten en áreas de valor ambiental para el Estado, el presente estudio de caso está basado en la gestión para la categorización de áreas protegidas privadas en la provincia de El Oro donde se analizara cada uno de los instrumentos imprescindibles en la gestión de áreas protegidas privadas APPRI en la provincia de El Oro en la declaratoria de subsistemas del Sistema Nacional de Áreas Protegidas. Esta investigación pretende brindar una guía práctica y accesible sobre los requisitos planteados y pasos a seguir por la Autoridad Ambiental Nacional para la categorización de áreas protegidas. Debido a la escasa información al alcance de la población nacional interesada en postular sus territorios como APPRI, se ha llegado a realizar una investigación de tipo bibliográfica basada en artículos científicos y datos tomados de la Dirección de Bosques del Ministerio del Ambiente y Agua, de esta manera nace la metodología aplicada a la investigación de enfoque bibliográfico mediante un análisis y síntesis para los cuales obtuvimos resultados a través de un organigrama que indica cada uno de los pasos solicitados para la categorización al subsistema de APPRI.
Keywords: AREA PROTEGIDA; GESTION; ECOSISTEMA